Gender key to food security and food safety - Sisto I. (Mainstreaming gender dimensions in water management for food security and food safety, 2007)
After reminding the global commitment for food security, this work gives a list of demographic, social, economic, political, institutional and security factors that is necessary to know to plan and implement gender-responsive food security programmes. Then, actions are proposed to ensure gender equality programming in food security. These actions can be assessed using a checklist available at the end of the study.
2. Regional Coordination Workshop of GEWAMED (Mainstreaming Gender Dimensions into Water Resources Development and Management in the Mediterranean Region), 2007/03/12-14, Larnaca (Cyprus)